A second record of Selenochlamys (Stylommatophora: Trigonochlamydidae) from Crimea - Ilya Turbanov; Igor Balashov (Malacologica Bohemoslovaca, 2015)
A live specimen of Selenochlamys was collected in a cave on the Ai-Petri massif of the Crimean Mountains in 2014. It is described and compared with the first Crimean specimen that was collected in 1989 on the Babugan massif. Both specimens are juvenile. Both seem to be more similar to S. ysbryda than S. pallida, and are considered as S. cf. ysbryda. Distribution and habitat preferences in Crimea are discussed. A second finding of Selenochlamys in Crimea suggests the first was not accidental and this slug is likely to be native in Crimea.